SOCIAL MEDIA AS A CONDUIT FOR TEACHER PROFESSIONAL DEVELOPMENT IN THE DIGITAL ERA: MYTHS, PROMISES OR REALITIES? - Alberth, Alberth; Mursalim, Mursalim; Siam, Siam; Suardika, I Ketut; Ino, La (TEFLIN Journal, 2018)
It is generally accepted that effective teacher professional development is critical to effective educational improvements and reforms of any educational institution. However, a conventional form of teacher professional development is constrained by time and space and, more often than not, there is a lack of perpetual support to teachers in the wake of a training program. An alternative way of teacher professional development therefore needs to be sought. This article argues that social media and all its facets open up new avenues for sustainable professional development and life-long learning in which case support can be obtained through virtual learning communities.